How can we breed for phosphate efficiency in maize (Zea mays)?. (17th September 2022) - Weiß, Thea M.; Li, Dongdong; Roller, Sandra; Liu, Wenxin; Hahn, Volker; Leiser, Willmar L.; Würschum, Tobias
Abstract: Future farming is required to produce high yields with reduced inputs. Increased fertilizer prices and policy goals underline the need to breed for nutrient‐efficient varieties. We therefore conducted a multienvironmental field trial comprising 400 maize genotypes, half elite lines and half doubled haploid lines from six European landraces and assessed yield parameters and corresponding phosphorus concentrations at two developmental stages. From these traits, we derived several measures for phosphate efficiency and evaluated them phenotypically and genetically. The results of this study revealed that ample variation for phosphate efficiency is present in maize. However, while elite material clearly outperformed all landraces with regard to yield‐related traits, some landrace genotypes indicated superior early development characteristics. The phosphate efficiency measures showed a complex genetic architecture, and hence, genomic selection appears best suited to assist their improvement. Taken together, breeding for phosphate efficiency is feasible but should be performed under the same conditions in which the crops are eventually grown because phosphate efficiency and what is deemed a sustainable P balance largely depends on the context.